Insecticidal effect of Essential Oils of Citrus limon, Cymbopogon citratus and Syzygium aromaticum and their Synergistic Combinations Against Anopheles Mosquitoes - Tunde Ayobami Owolabi; Philippine Chigozie Okubor; James Danga; Issa Onimisi (Acta Biologica Slovenica)
While synthetic insecticides offer effective pest control, their many side effects necessitate exploring alternatives, this study investigates the insecticidal potential of essential oils from lemon (Citrus limon), lemongrass (Cymbopogon citratus), and clove (Syzygium aromaticum) against Anopheles mosquitoes, a prime vector of malaria, a deadly global disease.